Forestry information exchange - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
In order to facilitate exchange of information and experience related to forestry extension, the Forestry Department of the United Nations Food and Agriculture Organization (FAO) is attempting a global survey of forestry extension organizations....